Organizational Justice: The Search for Fairness in the WorkplaceOrganizational Justice: The Search for Fairness in the Workplace, by Sheppard Blair H., Lewicki Roy J., and Minton John W.. New York: Lexington Books, 1992, 227 pp., cloth. - Folger, Robert (Academy of Management Review, 1994)
The article reviews the book “Organizational Justice: The Search for Fairness in the Workplace,” by Blair H. Sheppard, Roy J. Lewicki, and John W. Minton.